1996
DOI: 10.1021/ja951121f
|View full text |Cite
|
Sign up to set email alerts
|

Complexes of Lysine, Histidine, and Arginine with Sulfonated Azo Dyes:  Model Systems for Understanding the Biomolecular Recognition of Glycosaminoglycans by Proteins

Abstract: The X-ray crystal structures of six salts composed of amino acids and sulfonated azo dyes have been determined, four of them at low temperature (173 K). The compounds are dl-lysine/4-[(4-hydroxyphenyl)azo]benzenesulfonate (HABS) monohydrate (1), dl-lysine/7-hydroxy-8-(phenylazo)-1,3-naphthalenedisulfonate (Orange G) dihydrate (2), l-lysine/Orange G 1.5-hydrate (3), dl-histidine/Orange G trihydrate (4), l-histidine/Orange G trihydrate (5), and tosylarginine methyl ester (TAME)/4-[(2-hydroxy-6-tert-butyl-1-napht… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
45
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 59 publications
(34 reference statements)
3
45
0
Order By: Relevance
“…The spectrum shows several cross-peaks between the proton pairs of OG including those between protons of ring A and ring B. It is clear that the conformation of bound OG is significantly different from that found in x-ray crystal structure (11). In fact, if the crystal structure was maintained in the bound OG then none of the nuclear Overhauser effects between protons in ring A and ring B should have been observed.…”
Section: Resultsmentioning
confidence: 78%
See 2 more Smart Citations
“…The spectrum shows several cross-peaks between the proton pairs of OG including those between protons of ring A and ring B. It is clear that the conformation of bound OG is significantly different from that found in x-ray crystal structure (11). In fact, if the crystal structure was maintained in the bound OG then none of the nuclear Overhauser effects between protons in ring A and ring B should have been observed.…”
Section: Resultsmentioning
confidence: 78%
“…It is known that the sulfonated compounds interact with amino acids such as Arg, Lys, His, etc., via sulfonate oxygen and make direct or indirect hydrogen bonds with the side chain NH (11). A closer inspection of BPA sequence reveals the presence of such charged residues near Trp-135.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous x-ray crystal study of structures of salts composed of amino acids (like those of HSA) and sulfonated AZO dyes (like OII) has shown that short (Ͻ3 Å) intermolecular H-bonds between the dye sulfonate groups and neighboring amino acids (48). For OII:HSA complexes, we cannot provide in this work an x-ray structure; however, if such kinds of interactions between the SO 3 Ϫ group of OII and the amino acids of the protein happen as it does in comparable systems (48), it makes robust the complex avoiding its dissociation. In a previous study, using a smaller molecular probe, we found a very large docking of the guest within Table 2.…”
Section: Femtochemistry In Solutionmentioning
confidence: 99%
“…A rather homogeneous group is given by the sulfonate azo-dyes. Although no diffraction data at variable temperature are available, all the 11 structures retrieved [100][101][102] were interpreted and discussed as being N-H…O tautomers, a conclusion justified by the fact that their average structural data of C-O = 1.271 [7], N-N = 1.298 [6] and O…N = 2.51 [2] Å are typical of an equilibrium strongly shifted towards the N-H tautomeric form. As an example, bis(adenine)-7-hydroxy-8-(phenylazo)-1,3-naphtalene-disulfonate pentahydrate (LEZHIH) [100] is reported in Fig.…”
Section: -Diazenyl-2-naphthols (Classes VII and Vii')mentioning
confidence: 99%